Penentuan Nilai Frekuensi Natural Bangunan UPT Perpustakaan UNS dengan Sensor Accelerometer pada Handphone Android: Rio Riantana, Darsono, Agus Triyono - Rio Riantana Rio Riantana; Darsono Darsono; Agus Triyono Agus Triyono (Jurnal Fisika dan Aplikasinya, 2017)
Determination the value of buildings natural frequency of UPT perpustakaan UNS with Accelerometer sensor on an android phone has been done. The main sensor for recording micro tremor activity is Accelerometer sensor on the android phone. Microtremor activity recording is done on every building’s floor of UPT Perpustakaan UNS and on the surface of land outside the building. From micro tremor activity recording, the recorded data is sent to the server by telemetry method. The data were stored on the server then displayed in the graph on the micro tremor web monitoring. Microtremor data is processed with the FFT function to determine the dominant frequency. From the dominant frequency, we find the ratio of resonance of soil and building of UPT Perpustakaan UNS. From the calculation, the value of resonance ratio is 69.35 - 94.48% in the NS component and 70.42-98.61% in the EW component with low resonance status on each floor of the building.